(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2024)
The widespread use of the internet has resulted in the emergence of new business models across various industries. Companies such as Grab and Airbnb have experienced rapid growth by implementing internet-based approaches, thereby replacing traditional business models that did not rely on technological advancements. Consequently, several sectors, including education, are experiencing rapid transformations. The education sector, responsible for equipping individuals with the necessary skills, must adapt to these changing times. Previous research has demonstrated that an enhanced Learning Management System (LMS) can enhance student self-efficacy and time management skills. Technological advancements indicate that the adoption of cloud technology can boost productivity and effectiveness, while also reducing system costs significantly. This article aims to provide a comprehensive perspective on how the onCloud Learning Management System can assist the education industry in embracing a new business model that caters to the demands of the modern era. By examining previous studies in the relevant field, we explore how the LMS can be made adaptable to meet the diverse needs of its users while maintaining cost-effectiveness. Additionally, we evaluate how the inherent features of a cloud-based system contribute to achieving optimal performance in the LMS. This article proposes the adoption of the onCloud learning management system model as a means to enhance the overall functionality of the LMS. The findings indicate that the cloud-based learning management system model offers various learning benefits in the era of modern technology, while also accommodating the need for computing resources and ensuring the quality of the LMS. It is expected that this model will propel the learning management system to a higher level of improvement.